SISTEM AKUISISI DATA TINGGI GELOMBANG LAUT BERBASIS IOT - Mukhlisin Mukhlisin; Irvawansyah Irvawansyah; Ahmad Daniel; Andi Ambas Hafid; Burhan BJ (Jurnal Teknologi Terapan, 2023)
Ocean wave height data is very much needed in the maritime world to support fishing activities, transportation, and coastal life. Ocean wave heights are easy to change so it is difficult to obtain measurement data, we need a system that is able to observe the behavior and changes in ocean wave height that is accurate and easy to monitor. The aim of this research is to design a data acquisition system for ocean wave height that is able to work with real time conditions and able be monitored at any time. The methods of this research is quantitative research using an experimental design. The system design consisted of field observations and literature studies, procurement of tools and materials, tool design, tool testing, and research data collection. Data collection techniques are carried out by testing sensors and displays on the application. The results showed that the Sea Wave Height Data Acquisition System that has been designed can work with an error percentage of 1.26% and has a very high level of measurement accuracy with an accuracy percentage of 98.74%. The results of the performance test of the Sea Wave Height Data Acquisition System that has been designed to be able to detect, collect, send, process, and display ocean wave height result data in real time.